Quality of life meta‐analysis following coloanal anastomosis versus abdominoperineal resection for low rectal cancer. (6th March 2022) - Maguire, Barry; Clancy, Cillian; Connelly, Tara M.; Mehigan, Brian J.; McCormick, Paul; Altomare, Donato F.; Gosselink, Martijn Pieter; Larkin, John O.
Abstract: Aim: In low rectal cancers without sphincter involvement a permanent stoma can be avoided without compromising oncological safety. Functional outcomes following coloanal anastomosis (CAA) compared to abdominoperineal excision (APR) may be significantly different. This study examines all available comparative quality of life (QoL) data for patients undergoing CAA versus APR for low rectal cancer. Methods: Published studies with comparative data on QoL outcomes following CAA versus APR for low rectal cancer were extracted from electronic databases. The study was registered with PROSPERO and adhered to PRISMA (Preferred Reporting Items in Systematic Reviews and Meta‐analyses) guidelines. Data was combined using random‐effects models. Results: Seven comparative series examined QoL in 527 patients. There was no difference in the numbers receiving neoadjuvant radiotherapy in the APR and CAA groups (OR: 1.19, 95% CI: 0.78–1.81, p  = 0.43). CAA was associated with higher mean scores for physical functioning(std mean diff −7.08, 95% CI: −11.92 to −2.25, p  = 0.004) and body image (std. mean diff 11.11, 95% CI: 6.04–16.18, p  < 0.0001). Male sexual problems were significantly increased in patients who had undergone APR compared to CAA (std. mean diff −16.20, 95% CI: −25.76 to −6.64, p  = 0.0009). Patients who had an APR reported more fatigue, dyspnoea and appetite loss. Those who had a CAA reported higher scores for both constipation and diarrhoea. Discussion: It is reasonable to offer a CAA to motivated patients where oncological outcomes will not be threatened. QoL outcomes appear to be superior when intestinal continuity is maintained, and permanent stoma avoided.